Solvatochromism and Theoretical Studies of Dicyanobis(phenylpyridine)iridium(III) Complex Using Density Functional Theory - Noorshida Mohd Ali; Anthony J. H. M. Meijer; Michael D. Ward; Norlinda Daud; Norhayati Hashim; Illyas Md Isa (Indonesian Journal of Chemistry, 2021)
Luminescent cyanometallate [Ir(ppy)2(CN)2]– (ppy = C6H5C5H4N) has recently gained attention due to its desired photophysical properties. Our research group reported that the [Ir(ppy)2(CN)2]– has shown a negative solvatochromism like [Ru(bipy)(CN)4]2–, resulting in a blue-shift of the UV-Vis absorption bands in the water. Therefore, to gain insight into the specific solvent-solute interaction governed by the hydrogen bond in the solvation hydration shell, density functional theory (DFT) calculations were performed on the singlet ground state of the [Ir(ppy)2(CN)2]– and its solvent environment in the water at B3LYP level theory. It was demonstrated, seven water molecules provided a good description of the relevant spectra: IR and UV-Vis. The calculation reproduced the positions and intensities of the observed n(CºN) bands at 2069 and 2089 cm–1. The calculated MLCT transition wavelength was 366 nm vs. a measured value of 358 nm, differing by 8 nm. The study revealed the water molecules interacted with cyanide ligands through CN⋯H-OH type hydrogen bonds and water-water interactions (HO-H⋯OH2 type hydrogen bonds) were involved in the solvation hydration shell around the [Ir(ppy)2(CN)2]–.